HUBUNGAN MOTIVASI DENGAN KEPUASAN KERJA PEGAWAI - Yoberth Kornelius (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the relationship between motivation and job satisfaction of employees at the Palu Health Polytechnic. This research uses quantitative methods. The population of this study were all employees of the Palu Polytechnic, totaling 69 people. This research sample uses the census technique, so that the entire population is used as the research sample. Based on this, the sample of this study amounted to 69 respondents. Data collection techniques include observation, questionnaires, and documentation. Sources of data in this study sourced from primary data and secondary data. Analysis of the data using correlation analysis which aims to determine the relationship between the variables studied. The results showed that there was a relationship between motivation and job satisfaction of employees at the Palu Health Polytechnic with a weak level of relationship.